Myths and mysteries surrounding continuous spinal anaesthesia. (December 2017) - Ye, Madong; Seet, Edwin; Kumar, Chandra M.
Abstract: Continuous Spinal Anaesthesia (CSA) is as old as single-shot spinal anaesthesia but it is used mainly by enthusiasts in high risk patients. It remains an underutilized method in current anaesthesia practice because of the myths and mysteries surrounding its application. This article tries to unravel some of the pertinent myths and mysteries behind this anaesthesia technique.